Effects of tillage activities on leaf area index in a Tectona grandis plantation in northern Costa Rica - Valverde, Juan Carlos; Guevara-Bonilla, Mario; Arias, Dagoberto; Briceño, Elemer; Esquivel, Edwin (Instituto de Ecología, A.C., 2017)
Tectona grandis is one of the species most used in reforestation projects in Costa Rica, and it has been planted on sites with problems of soil compaction layers that delay plantation growth; for this reason it is necessary to develop activities that improve soil conditions and promote productivity. The present study evaluated the effects on diameter, total height and leaf area index (LAI) of eight tillage treatments (witness, witness with dolomite, tillage with one, three and five chisels both 25 cm and 40 cm deep in combination with dolomite) applied during 2013 in a T. grandis plantation. Results showed that three years after tillage no significant differences were found in diameter and tree height (in average 11,74 cm and 11,1 m respectively). Instead the LAI showed the formation of two groups of treatments, one formed by the witness and witness with dolomite and the other with the tillage treatments. The first group presented LAI less than 3,80 m2 m-2, with correlations of leaf area index-height below 15% and allometric models with high standard errors, this is due to the heterogeneity of the individuals caused by the stress generated by the conditions of soil compaction. On the other hand, individuals with soil tillage presented LAI superior to 4,5 m2 m-2, with correlations of LAI-height greater than 56% and allometric models with errors standard under 0,20; the increase is due to the recovery process of the individual growth caused by the improvement of soil properties.